Dukungan Orang Tua terhadap Motivasi Berprestasi Pada Atlet Muda Sepakbola Di Pekanbaru - Dede Basriyanto; Ardian Adi Putra; thahroni . (Psychopolytan : Jurnal Psikologi, 2019)
This study aims to determine the support of parents with achievement motivation for young athletes in soccer sports in the city of Pekanbaru. Data collection uses a scale of parental support with a scale of achievement motivation. The research subjects were 100 young athletes in the city of Pekanbaru. Subjects are selected using the Sampling quota method. The research data was processed using correlation coefficient Pearson product moment. The results showed an association between parental support and achievement motivation with significant = 0.035 (p <0.05). Parental support contributes to an influence of 40% to achievement motivation in young athletes.